Triple-band antenna using double periodic CRLH resonator on coplanar waveguide - Mohan, Manoj Prabhakar (2022)
The uniplanar implementation of double periodic composite right/left-handed (DPCRLH) symmetric unit cell is realized using coplanar waveguide and its analysis with parameter extraction are studied. DPCRLH symmetric unit cell is then experimentally validated. The open-circuited DPCRLH resonator is formed from the DPCRLH unit cell which exhibited five resonance points. The simulated resonant frequencies of the resonator are 1.5494, 2.1968, 3.5072, 5.0438 and 6.089 GHz. A triple-band antenna is designed from the last three resonant frequencies of the resonator. The antenna is horizontally polarized in all three bands. The measured co-polarized gain of the antenna at the central frequencies of the three bands are 1.52 dBi (3.59 GHz), 3.67 dBi (5.1694 GHz) and 1.78 dBi (6.0925 GHz), respectively.